2020
DOI: 10.1111/1759-7714.13397
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0038467 regulates lipopolysaccharide‐induced inflammatory injury in human bronchial epithelial cells through sponging miR‐338‐3p

Abstract: Background: Pneumonia is a common acute lower respiratory infection in children and elders. Circular RNAs (circRNAs) have recently been uncovered to play important roles in pneumonia. However, the function and mechanism of circ_0038467 in pneumonia remain elusive. Methods: Cell viability and apoptosis were determined using the Cell Counting Kit-8 (CCK-8) assay and flow cytometry, respectively. The levels of interleukin 6 (IL-6), IL-8 and IL-1β were detected by enzyme-linked immunosorbent assay (ELISA). Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 36 publications
(39 reference statements)
1
20
0
Order By: Relevance
“…Liu et al reported that Circ_0038467 was upregulated in human bronchial epithelial cells by LPS treatment and the knockdown of Circ_0038467 protected cells from LPS-induced injury (15), suggesting that Circ_0038467 may promote LPS-induce cell injury. Consistently, our study also showed that LPS treatment increased the expression of Circ_0038467 in chondrocytes in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al reported that Circ_0038467 was upregulated in human bronchial epithelial cells by LPS treatment and the knockdown of Circ_0038467 protected cells from LPS-induced injury (15), suggesting that Circ_0038467 may promote LPS-induce cell injury. Consistently, our study also showed that LPS treatment increased the expression of Circ_0038467 in chondrocytes in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In OA, CircRNAs not only participates in disease progression, but also serves as biomarkers for disease diagnosis and prognosis (13), suggesting the potential roles of circRNAs as promising targets for OA targeted therapy. The development of osteoarthritis (OA) requires the involvement of LPS-induced in ammation (14), in which circRNA Circ_0038467 plays a critical role (15), suggesting the involvement of Circ_0038467 in OA. Our deep sequence analysis revealed the altered expression of Circ_0038467 and its inverse correlation with miR-203 (data not shown), which is also a critical player in LPS-induced cell injury (16).…”
Section: Introductionmentioning
confidence: 99%
“…The STAT3 signaling pathway is pivotal for the inflammatory response ( 31 ). During acute inflammatory injury, the STAT3 signaling pathway is implicated in lung injury ( 32 ) and LPS-induced inflammatory injury, as well as in the circular RNA (circ)_0038467/miR-338-3p axis ( 33 ). The results of the present study demonstrated that LPS significantly increased STAT3 activation compared with the control group, which was reversed by transfection with let7f-5p mimic.…”
Section: Discussionmentioning
confidence: 99%
“…circ‐0038467 is postulated to have acted as a sponge of miR‐338‐3p to regulate LPS‐induced inflammatory injury. The JAK/STAT3 signalling pathway appeared to be involved in the regulation of the circ‐0038467/miR‐338‐3p axis 122 . Neodymium oxide (Nd 2 O 3 ) can be used to induce inflammatory damage of 16HBE cells, and the up‐regulated circ‐0039411 is involved in the inflammatory promotion of 16HBE cells by the circ‐0039411/miR‐93‐5p/STAT3 pathway 123 .…”
Section: Circrnas In Childhood‐related Diseasesmentioning
confidence: 99%